2018
DOI: 10.1007/s40615-018-0461-6
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Harassment, Ethnic Identity Centrality, and Well-Being

Abstract: In this study, we examined the direct effect of (positive vs. negative) evaluation of potentially harassing experiences due to ethnic background on impaired well-being as well as the moderating effect of ethnic identity centrality on the relationship between (lower vs. higher) frequency of potentially harassing experiences and impaired well-being. Using a gender-balanced sample with equal proportions of black and minority ethnic and white undergraduate students (N = 240), we found that, expectedly, ethnic iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This could obviously lead to hypervigilance when faced with subsequent threats. For example, in a U.K. study, the centrality of ethnic identity was found to be a risk factor for ethnic minority members and people of African descent, but a protective resource for white people; however, the centrality of ethnic identity increased the relationship between higher frequency of harassment experiences and poor well-being in all groups (Wolfram et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This could obviously lead to hypervigilance when faced with subsequent threats. For example, in a U.K. study, the centrality of ethnic identity was found to be a risk factor for ethnic minority members and people of African descent, but a protective resource for white people; however, the centrality of ethnic identity increased the relationship between higher frequency of harassment experiences and poor well-being in all groups (Wolfram et al, 2018).…”
Section: Discussionmentioning
confidence: 99%